Pengaruh Penggunaan Media Sosial sebagai Strategi Promosi terhadap Peningkatan Penjualan di PT. Destini Marine Safety - Immanuel Zai; Mashita Ayuni (FKIP, Universitas Palangka Raya, 2025)
This research aims to analyze the influence of using social media as a promotional strategy on increasing sales at PT. Destini Marine Safety. Along with the development of digital technology, social media has become an effective promotional tool for companies in expanding market reach and increasing interaction with consumers. The research method used is a quantitative method with a descriptive approach. Data was collected through interviews and observations of the company's promotional activities on social media. The research results show that the use of social media as a promotional strategy has a significant effect on increasing sales. Platforms like Instagram help companies disseminate product information, build relationships with customers, and increase customer loyalty. With increased interaction and exposure through social media, PT. Destini Marine Safety experienced positive sales growth. This research recommends optimizing the use of creative and interactive content to increase the effectiveness of promotions on social media.